Metal-as-insulation HTS coils. (1st July 2022) - Lécrevisse, Thibault; Chaud, Xavier; Fazilleau, Philippe; Genot, Clément; Song, Jung-Bin
Abstract: In this article, we summarize what we have learned about metal-as-insulation (MI) winding behavior and technical challenges. High-temperature superconductor (HTS) materials are highly thermally stable. This feature compared to classical low temperature superconductor (LTS) enables the use of MI technology to improve the protection against quenches. We firstly present a review of what has been done worldwide since 2011, which is the first time that a co-winding of a metallic tape without insulation was used in HTS pancake coils. In this review we also focus on the turn-to-turn contact resistivity parameter and the ranges obtained by groups worldwide. Then, we give details of our NOUGAT insert, a LNCMI-CEA-Néel Institute MI HTS insert built in 2018. We describe the specific conception of the magnet including the compact magnetic shielding. The high number of tests performed in high resistive background fields between 2018 and 2021 gives us a unique data set on this technology for ultra-high field (UHF) magnets; even in case of a background field fast drop at 19 T. This magnet is the first REBCO solenoid of this size using this technology, and tested intensively at such high magnetic fields (up to 32.5 T) so far. Finally, we discuss about the self-protection feature of MI coils and we propose a passive protection way for high turn-to-turn resistivity values.